The Moral Struggle of the Theory of Reversal of the Burden of Proof in the Accountability of Directors Based on the Principle of the Business Judgment Rule in Achieving Justice - Fauzi, Engrina; Wahyuni, Sry (LPPM Universitas Ekasakti, 2025)
The business judgment rule (BJR) shields corporate policy-making and managerial decisions from scrutiny. Under this doctrine, directors are not legally liable for business decisions that later result in losses, provided the decisions are made in good faith, for proper purposes, on a rational basis, and with due care. BJR is welcomed because it protects directors who must act swiftly in a dynamic business environment. Yet its application often employs a reversal of the burden of proof (omkering van bewijs), shifting proof obligations. This research argues that the conventional presumption of innocence has been displaced by a presumption of guilt through the reversal of burdens in corruption cases, so that accused persons are treated as having committed a “presumption of corruption.” Corporate losses in such situations represent ordinary business risk, not wrongdoing; therefore, extraordinary enforcement measures are unnecessary and would only intensify directors’ evidentiary burdens. The reverse-burden rationale is typically grounded in alleged losses to state finances and the difficulty of eradicating corruption. Even so, corporate losses should not be reclassified as a “serious crime” that triggers extraordinary measures. The findings reveal a rigid separation of law and morality in the application of reversed burdens within the BJR framework. Generalization is unwarranted: the mechanism has both benefits and drawbacks. It aids law enforcement in combating corruption, but it is less effective for directors acting in good faith, because losses arising from business risk may be construed as fault. Consequently, criminal penalties can be imposed too readily on directors, owing to the heavy burden of proof placed upon them.